A model for spatial planning of site and building using BIM methodology - Ustinovichius, Leonas; Peckienė, Aurelija; Popov, Vladimir (Journal of Civil Engineering and Management, 2017)
In this day and age, as information technology develops at an intense pace, the construction sector cannot afford to fall behind. The term “building information modelling”, or BIM, is now used increasingly more frequently. BIM covers the entire life span of a building – from planning to demolition. However, it should not be forgotten, that without a site, there can be no building. Territorial planning documents establish certain requirements for both the site itself and the buildings to be built within its boundaries. At present, territorial planning and building design are, for the most part, carried out as separate processes. In order to develop a more rational and effective process for the execution of a construction project, more attention should be paid to the stage of initial site and building planning (spatial planning). The requirements established by territorial planning documents must be taken into account at the initial site and building planning stage. A spatial planning model for buildings associated with a territorial planning system was developed as part of this study and could be used as a basis for further building information modelling. First published online: 21 Nov 2016